Survey of grid-connected photovoltaic inverters and related systems - Rahim, N.A.; Saidur, Rahman; Solangi, K.H.; Othman, M.; Amin, N. (Clean Technologies and Environmental Policy, 2012)
Grid-connected photovoltaic (PV) inverter technology has advanced since it first attracted the attention of policy makers. The objective of this article is to present a survey of grid-connected PV inverters and their present technology in Malaysia. Surveyed here are 186 PV inverter products from 22 manufacturers, their power factors, system THDs, efficiencies, power inputs (from PV array), costs, sizes, and protections investigated, and their datasheets collected from various manufacturers in Europe, North America, and Asia. The data are compared within regions and subject headings. Discussed are the lowering of cost, the raising of efficiency levels, and reliability improvement.